Consumer Risk Perception of Food Contamination as an Influencer to Purchase Irradiated Ground Beef, Chicken, and Leafy Greens – United States, October 2022 - Michael Ablan; Tamara N. Crawford; Michelle Canning; Misha Robyn; Katherine E. Marshall (Journal of Food Protection)
Foodborne illness continues to be a substantial public health concern in the United States with contaminated ground beef, chicken, and leafy greens identified as important sources of illnesses and outbreaks. These foods also have been identified by consumers as foods that are likely to carry germs that can make people sick. Food irradiation is a promising tool to enhance food safety. Despite this, there has been limited application of food irradiation in the U.S. During October 7–9, 2022, we licensed data from a Porter Novelli Public Services survey (N = 1,008) to examine consumer risk perception of contamination of ground beef, chicken, and leafy greens with pathogens, and the potential influence risk perception has on purchasing irradiated versions of these foods. Among respondents familiar with food irradiation, a higher proportion of those who believed ground beef and leafy greens were likely contaminated also indicated they were likely to consider purchasing irradiated ground beef (55.6% vs 35.4%; p = 0.0061) and leafy greens (60.8% vs 36.1%; p ≤ 0.0001) compared with those who did not; chicken was not significant (58.6% vs 45.4%; p = 0.0727). This survey demonstrated the importance of risk perception as an influencer on a consumer’s decision to purchase irradiated foods.